PENGEMBANGAN DAYA TARIK DESA WISATA DI KABUPATEN BADUNG DENGAN PENDEKATAN POSTFORDISM - Suwita Yanti, Ayu; Eka Sudarmawan, I Wayan; Hadi Purnantara, I Made; Ayu Eka Suwintari, I Gusti (CV. Lafadz Jaya, 2024)
The aim of this research is to examine tourism development in Badung Regency, Bali, with a focus on the concept of Tourism Village and the application of the principles of postfordism. Referring to the Badung Regency Regional Regulations relating to Tourist Attractions and Tourist Villages, Badung has accommodated a number of diverse tourist attractions, including natural beauty, cultural heritage and adventure destinations. This research methodology adopts a literature study approach, which is a data collection method by utilizing related literature from various sources. Referring to the Tourism Village concept, Badung is identified as having integrated local economic growth, cultural preservation and environmental protection in tourism development. This approach not only generates economic benefits, but also strengthens cultural and environmental aspects, creating an unforgettable tourism experience for visitors. Through the principles of postfordism, Badung embodies a model of social and political regulation that regulates the relationship between tourist consumption, local economic growth, and cultural and environmental preservation. Thus, the development of Badung tourism through the Tourism Village concept reflects a holistic and successful economic strategy in creating sustainability in the tourism sector.